Research on Gas Extraction Technology of Directional Long Borehole in Ultrathick Coal Seam - Yaobin Li; Tao Jiang; Xin Guo (Geofluids)
Gas extraction is an important way to control gas disasters. The effect of traditional gas extraction drilling on ultrathick coal seam is not well. In order to improve the rate of gas extraction, directional long drilling is used to replace conventional drilling for coal seam gas extraction. Through the combination of numerical simulation and field experimentation, the stress distribution around borehole is analyzed, and the influence of different time, different gas pressure, different negative pressure of extraction, and different permeability of coal body on directional borehole is simulated. According to the experimentation of Baode Mine, the data of gas drainage volume of conventional directional drilling are recorded and analyzed. The results indicate that the directional drilling is more suitable for Baode Mine 81306 working face of coal seam 8 gas extraction operation. Directional drilling is better than conventional drilling in work, with good drainage stability and large gas drainage volume, which can greatly reduce the outburst time and improve the gas drainage rate.